2022
DOI: 10.1186/s12936-021-04029-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating performance of multiplex real time PCR for the diagnosis of malaria at elimination targeted low transmission settings of Ethiopia

Abstract: Background Malaria incidence has declined in Ethiopia in the past 10 years. Current malaria diagnostic tests, including light microscopy and rapid antigen-detecting diagnostic tests (RDTs) cannot reliably detect low-density infections. Studies have shown that nucleic acid amplification tests are highly sensitive and specific in detecting malaria infection. This study took place with the aim of evaluating the performance of multiplex real time PCR for the diagnosis of malaria using patient sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This study showed that the performance of RDT and microscopy decreased as age increased, agreeing with previous studies [ 20 , 36 , 47 ]; this could be explained by age-dependent immunity from frequent exposure [ 20 , 62 ], which could be independent of parasite density [ 63 ]. Interestingly, this study showed that RDT and microscopy had significantly higher sensitivity among non-Saudi patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study showed that the performance of RDT and microscopy decreased as age increased, agreeing with previous studies [ 20 , 36 , 47 ]; this could be explained by age-dependent immunity from frequent exposure [ 20 , 62 ], which could be independent of parasite density [ 63 ]. Interestingly, this study showed that RDT and microscopy had significantly higher sensitivity among non-Saudi patients.…”
Section: Discussionsupporting
confidence: 92%
“…It also accurately detects mixed-species infections; thus, it has been widely used for diagnosis, epidemiological surveys, and drug efficacy trials [ 10 , 20 ]. Furthermore, several studies have used nested PCR as a reference method to assess the performance of malaria diagnostics in different settings [ 20 , 22 , 33 , 34 , 35 , 36 ]. In this study, PCR was superior to microscopy and RDT for diagnosing P. falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies that utilized DBS for parasite detection relied on quantitative PCR of the Plasmodium 18S rRNA coding genes [22][23][24][25][26][27][28][29][30][31], but DNA-based DBS tests are less sensitive than qRT-PCR for the highly expressed Plasmodium 18S rRNAs, which means more infections may be missed by standard DNA-based tests [32]. Ultrasensitive DNA-based tests, such as var-ATS as well as 18S qRT-PCR assays can detect low levels of parasites from DBS [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Thin and thick blood slides remained as gold standard for malaria diagnosis to date (Mathison and Pritt 2017 ) (Belachew et al 2022 ). The rapid diagnostic tests (RDTs) and microscope are the common tests that are routinely used for the management of malaria cases in Tanzania, although microscope remained to be the gold standard [11] [12].…”
Section: Discussionmentioning
confidence: 99%